Representation of Current Sociocultural Realities in German Society: Thematic Group of Internet Memes OUTSIDER — LOCAL - L. N. Rebrina (Научный диалог, 2023)
This article presents an analysis of internet memes in Germany from 2020—2023, focusing on the thematic group “Outsider — Local”. The study examines various characteristics of these memes, such as their place and date of posting, “genetics”, precedent phenomenon, addressing, field structure, object and subject of criticism, interaction of visual and verbal series, patterns of meaning generation, sources of humor, and genre. The article identifies four subgroups of memes, which include criticism of political subjects (in defense of migrants), criticism of political subjects (against migrants), criticism of migrants, and criticism of local ethnic Germans. The study finds that social groups themselves, such as migrants and typical Germans, are the most frequently criticized objects. Additionally, the authorities are criticized for their insufficient or excessive support of migrants, while typical Germans are criticized for their cultural standards. The most frequent subjects of criticism for migrants include their large numbers, low integration into German society, criminal tendencies, pretentiousness, and disrespect for other cultures. The article notes that intercultural memes are infrequent, while borrowed memes that refer to recognizable characters and contemporary precedent phenomena with broad addressing dominate. Finally, the dominant genre varieties are macros and edvices.